2011
DOI: 10.1111/j.1365-2133.2011.10462.x
|View full text |Cite
|
Sign up to set email alerts
|

Varicella‐zoster virus antigen expression of eccrine gland and duct epithelium in herpes zoster lesions

Abstract: Immunohistochemical detection of VZV gE in eccrine epithelium can be a subtle clue to the diagnosis of HZ which displays most unusual manifestations, and VZV-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…In most cases, the characteristic features of HZ rash establish the clinical diagnosis. 3 Because VZV gE is an essential late protein expressed on the cell membrane during lytic infection and is a predominant component of the virion envelope, 24,25 immunohistochemical detection of VZV gE in these lesions, either cutaneous or gastrointestinal, suggests VZV involvement in the development of these lesions. These lesions encompass folliculitis, 20 syringitis, verruciform lesions, 21 nodular lesions, 22 intracranial hemorrhage, 23 and acute abdomen.…”
Section: During An Episode Of He Rpes Zostermentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the characteristic features of HZ rash establish the clinical diagnosis. 3 Because VZV gE is an essential late protein expressed on the cell membrane during lytic infection and is a predominant component of the virion envelope, 24,25 immunohistochemical detection of VZV gE in these lesions, either cutaneous or gastrointestinal, suggests VZV involvement in the development of these lesions. These lesions encompass folliculitis, 20 syringitis, verruciform lesions, 21 nodular lesions, 22 intracranial hemorrhage, 23 and acute abdomen.…”
Section: During An Episode Of He Rpes Zostermentioning
confidence: 99%
“…3 [NOTE: Rather than "manuscript submitted," please report the "authors name(s), personal communication."] Indeed, careful follow-up of patients for years may reveal the transformation of an immature form of disease into a more classic or typical form of disease; typical examples of such transitions are often reported and include conversion from granuloma annulare to sarcoidosis and from discoid lupus erythematosus to systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that VZV antigen expression is observed in the cytoplasm of eccrine gland and duct epithelium in the majority of HZ lesions up until 2.5 years after the onset of HZ [8]. These findings prompted us to investigate whether VZV antigens could be detected in zosteriform and linear LP lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Biopsy specimens were obtained from these LP lesions of 6 additional patients with informed consent. To detect VZV antigens in these LP lesions, immunohistochemical examinations were performed using paraffin sections of formalin-fixed materials, murine monoclonal antibody directed to the VZV envelope glycoprotein E (gE; Chemicon Inc., Temecula, Calif., USA), and the Dako Envision System (Dako, Calif., USA), as described previously [8]. Briefly, 5-µm sections were deparaffinized and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation